SATUA KATUTURAN I KEDIS SANGSIAH TEKEN I BOJOG SUMBER PENGUATAN KARAKTER ANAK - Komang Puteri Yadnya Diari (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
The existence of satua as one of cultural heritages in Balinese society has greatcharacterised educational values, which could be early formula in giving the characterisededucation towards the children by providing them a lot interesting stories. One of them isKatuturan I Kedis Sangsiah teken I Bojog. The problem which is focused in this research is toconcern about the values in this story which are aimed to describe the whole values of thecharacterised education. Theories which are used in this research in the theory of Thomas Lickonaand the structural approach toward the literature works. Method which is used in this researchis qualitative descriptive method, with the research model using content analysis. The techniqueof colleting data for this research is the recording note. The data source is the spoken data fromthe informant, towards the satua as the spoken literature. The techniques of analyzing data forthis research are (1) the transcription of recorded data (2) translation, (3) Data classification,(4) Structure analysis, (5) Data test, the result is the conclusion of the research, that in the satuaKatuturan I Kedis Sangsiah teken I Bojog provides great characterised educational values; thevalue of tattwa about karma phala, about how we think, say an do the good deeds ( Tri KayaParisudha). Besides religious value, there are also the value of social educations such as justice,self autonomy and wisdom.